Rapid screening and quantification of heavy metals in traditional Chinese herbal medicines using monochromatic excitation energy dispersive X-ray fluorescence spectrometry - Ma, Xing; Hua, Marti Z; Ji, Chao; Zhang, Jing; Shi, Rui; Xiao, Yabing; Liu, Xiaojing; He, Xiahong; Zheng, Wenjie; Lu, Xiaonan (Analyst (London), 2022)
Traditional Chinese herbal medicines are subject to heavy metal contamination. Standard detection methods are too complicated, time-consuming, and expensive for routine analysis, so low-cost methods are in high demand for rapid on-site screening. This study reports a high-sensitivity X-ray fluorescence (HS-XRF) method to determine As, Pb, and Cd residues simultaneously in herbal medicines. It couples monochromatic excitation energy dispersive X-ray fluorescence spectrometry and the fast fundamental parameters method. Each test takes only 10-30 min and costs 1/10th to 1/5th of the standard method. The detection limits, precision and accuracy were evaluated using different approaches, and application notes in practice are also proposed. This study is the first attempt to establish and evaluate HS-XRF in analyzing multiple heavy metals in herbal medicines. This rapid screening method would promote the testing efficiency and thus improve the monitoring of heavy metal contamination in herbal medicines. Detection of heavy metal residues in herbal medicines by a high-sensitivity X-ray fluorescence method that couples monochromatic excitation energy dispersive X-ray fluorescence spectrometry and the fast fundamental parameters method.